Factors associated to the vaginal flow syndrome in gestants of a primary care center of Lima, Peru - Salinas-Terrones, Lilian (2021)
Objective: To determine the factors associated with the presence of vaginal discharge syndrome during pregnancy in the Carlos Cueto Fernandini health center. Materials and methods: Observational, analytical cross-sectional study. We evaluated 100 clinical records of pregnant women attended at the health center, divided into users with vaginal discharge syndrome and without the syndrome. The relationship between the variables was evaluated using the 95% confidence-rate test. Results: The variables that were associated with the risk factors were presenting urinary tract infection during pregnancy (OR = 2.67, 95% CI: 1.00 to 7.31), presenting moderate inflammation in the cervix (OR = 4.04, 95% CI: 1.11, -18.21), the beginning of sexual intercourse before age 16 (OR = 3.24, 95% CI: 0.86-14.92), having had more than two sexual partners (OR = 9.2 ; IC95%: 13.19-28.57), having a history of STIs (OR = 6.31, IC95%: 2.41-16.92) and having been a victim of intrafamily violence (OR = 4.95, 95% CI: 1.19-28.84). While having only one sexual partner (OR = 0.25, 95% CI: 0.09-0.69) and not having any type of comorbidity in pregnancy (OR = 0.44, 95% CI: 0.18-0.82) were associated as protective factors. Conclusions: The symptoms associated with the vaginal vein syndrome were: presentation of a urinary infection during pregnancy, moderate inflammation of the cancer, initiation of sexual intercourse before the age of 16, having more than two sexual partners, having a history of STIs and having been victim of family violence.